Rachael Ray's look + cook : 100 can't-miss main courses in pictures - Ray, Rachael (New York : Clarkson Potter, 2010)
An extensively photographed volume of recipes includes simple main courses and complementary starters and sides for everyday meals.
"125 more all-new recipes: interactive 30-minute meals, sides, sauces & yum-o menus!"
Includes index.
Keywords: Quick and easy cooking; Quick and easy cooking; Cookbooks